PENGARUH PROMOTIONAL TOOLS TERHADAP CONSUMER BUYING BEHAVIOR DI PASAR RITEL PADA PELANGGAN SUZUYA MALL KOTA BANDA ACEH - Muhammad Zaki Mubarak; Syarifah Evi Zuhra (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2019)
Abstract: This study aims to measure the Effect of Promotional Tools on Consumer Buying Behavior in Retail Markets at Customers of Suzuya Mall, Banda Aceh City. The samples used in this study were people who had shopped at the Suzuya mall in Banda Aceh, totaling 140 respondents. Data collection equipment used in this study is a questionnaire. The sampling technique used was purposive sampling. The method of analysis of data testing and analysis is done by using version 22 of the SPSS (Statistical Package for Social Science) device with multiple regression formulations. The results of this research show that Coupon has a significant positive effect on Consumer Buying Behavior, then Price Discount has a significant positive effect on Consumer Buying Behavior, then Free Sample has a significant positive effect on Consumer Buying Behavior, and Buy One Get One Free has a significant positive effect on Consumer Buying Behavior.Keywords: Promotional Tools, Coupon, Price Discount, Free Sample, Buy One Get One Free, Consumer Buying Behavior.